Comparison of Automated Atlas-Based Segmentation Software for Postoperative Prostate Cancer Radiotherapy - Delpon, Grégory; Escande, Alexandre; Ruef, Timothée; Darréon, Julien; Fontaine, Jimmy; Noblet, Caroline; Supiot, Stéphane; Lacornerie, Thomas; Pasquier, David (Frontiers in Oncology, 2016)
Automated atlas-based segmentation algorithms present the potential to reduce the variability in volume delineation. Several vendors offer software that are mainly used for cranial, head and neck and prostate cases. The present study will compare the contours produced by a radiation oncologist to the contours computed by different automated atlas-based segmentation algorithms for prostate bed cases, including femoral heads, bladder and rectum. Contour comparison was evaluated by different metrics such as volume ratio, Dice coefficient and Hausdorff distance. Results depended on the volume of interest and showed some discrepancies between the different software. Automatic contours could be a good starting point for the delineation of organs since efficient editing tools are provided by different vendors. It should become an important help in the next few years for organ at risk delineation.